Mental Health and Foundational Academic Behaviours: Pieces of the Academic Success Puzzle - Kapil, Meg; Rostampour, Ramin; Hadwin, Allyson; Miller, Mariel; MacDonald, Stuart W.S. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2025)
The interplay between mental health and academic behaviours has been understudied. This study examined the relationship between foundational academic behaviours (e.g., attending class and meeting assignment deadlines), student mental health and well-being, and academic performance. Participants consisted of 229 students (52.6% female) who participated in a first-year introductory learning-to-learn course. Findings from structural equation modelling indicated: (a) higher levels of foundational academic behaviours predicted higher GPA, (b) higher levels of emotional well-being predicted higher levels of foundational academic behaviours and higher GPA, and (c) foundational academic behaviours mediated the relationship between emotional well-being and GPA. Findings affirm the integral role of mental health in academic performance and highlight the mediating role of foundational academic behaviours in this relationship. The association between emotional well-being and foundational academic behaviours underscores the multifaceted nature of academic performance and the importance of considering both mental health and foundational academic behaviours in academic success. Findings from this study suggest that managing behaviours that facilitate engagement in academic tasks, and mental health as a potential internal condition for learning, are both important pieces to the academic success puzzle.